Kualitas Sperma pada Laki-Laki Defisiensi Vitamin D di Palembang - Maya Eka Apriyanti; Yusuf Effendi; Zen Hafy (Syntax Literate, 2023)
Vitamin D deficiency may play some roles in male infertility. Abundant vitamin D receptors exist in male reproductive tracts, implying some significant functions of vitamin D in spermatogenesis and/or testosterone synthesis. This study aims to measure sperm parameters in males with vitamin D deficiency in Palembang, South Sumatra. This study was a conducted as observational, cross-sectional descriptive study on single mother and child hospital in Palembang. Subjects’ serum vitamin D was measured in an accredited external clinical laboratory and sperm samples were collected and examined in same laboratory according to standard protocols. Median age of subject was 30,0 (24-49) years old. Mean serum vitamin D concentration was 21.372 ± 4.202 ng/mL. Median sperm concentration was 21.75 (0.00-137.00) millions/mL. Median sperm count was 66.14 (0.00-370.80) millions. Average progressive motility was 35.64 ± 18.573%. Median normal morphology was 5.00 (0.00-7.00)%. Normal sperm parameters observed in this study implicated vitamin D plays no significant role in sperm quality.